2022
DOI: 10.1002/ctm2.1099
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the pentraxin 3/CD44 interaction attenuates lung injury‐induced fibrosis

Abstract: 1. PTX3 promotes fibroblast activation and pulmonary fibrosis. 2. CD44 mediates PTX3-induced fibrotic activation and regulation in lung injury. 3. αPTX3i is a novel and promising candidate for fILD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…These data are consistent with a previous study in which Ptx3 promoted breast cancer stemness, migration, and invasion [ 19 ]. More importantly, it is reportedly that the Ptx3 can bind to CD44 transmembrane receptor in lung fibroblasts to activate fibrotic scar-related gene expression, such as fibronectin, collagen I, and α-SMA [ 16 ]. Given the relationship between Ptx3 and fibrotic scar formation in spinal cord injury, we speculate that Ptx3 can activate meningeal fibroblasts to express fibrotic scar-related gene expression through CD44 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with a previous study in which Ptx3 promoted breast cancer stemness, migration, and invasion [ 19 ]. More importantly, it is reportedly that the Ptx3 can bind to CD44 transmembrane receptor in lung fibroblasts to activate fibrotic scar-related gene expression, such as fibronectin, collagen I, and α-SMA [ 16 ]. Given the relationship between Ptx3 and fibrotic scar formation in spinal cord injury, we speculate that Ptx3 can activate meningeal fibroblasts to express fibrotic scar-related gene expression through CD44 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, secreted Ptx3 in the extracellular environment promotes surrounding cell migration [13], inflammation [14], and is correlated with fibrosis [15]. Currently, it has been reported that Ptx3 activates lung fibroblasts to differentiate myofibroblasts through binding to CD44 in which increase ECM deposition and express fibrotic markers (e.g., fibronectin, collagen I, and α-SMA) to form fibrotic scar [16]. However, the molecular mechanism whereby Ptx3 affects fibrotic scar formation after contusive spinal cord injury has yet to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Pentraxin-3 is a component of the innate immune system and participates in resistance to inflammation and microorganisms (42). It is induced by primary proinflammatory cytokines, mainly IL-1 and tumor necrosis factor-α, and toll-like receptor agonists in different cell types, such as myeloid (mononuclear phagocytes, neutrophils, and dendritic cells), endothelial and stromal cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Masson’s trichrome staining is commonly used to detect collagen fiber formation in tissues [ 52 ]. The formation of collagen fibers was evaluated using Masson’s trichrome staining, per the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was measured using CCK-8 [ 52 , 54 ] (CCK-8, Dojindo, Japan), per the manufacturer’s protocols. Briefly, MRC-5 cells were seeded in 96-well plates (1.5 × 10 4 ) for 24 h. Then, the cells were serum starved in serum-free medium for 24 h. Next, the Prophylactic administration cells were incubated in MEM containing different CEP concentrations (0, 0.1, 0.2, 0.4, 0.8, 1, 2, 4, 8, and 16 μg/mL) for 1 h. Cells were subsequently exposed to 10 ng/mL TGF-β1 with or without CEP for 48 h. In contrast, for therapeutic administration, cells were exposed to 10 ng/mL TGF-β1 for 1 h, followed by the same CEP as prophylactic administration, and continued to be cultured for 48 h. Next, the media was replaced with MEM supplemented with 10% CCK-8 reagent, 100 μL of basal medium (MEM supplemented with 100 U/mL penicillin, 100 μg/mL streptomycin and Earle’s Balanced Salt Solution) mixed with CCK8 dye was added to the wells (CCK8 dye: MEM basal medium = 1:10), and the cells were cultured for another 2 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%